The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1017/s0031182005008474
|View full text |Cite
|
Sign up to set email alerts
|

High polymorphism in genes encoding antigen B from human infecting strains of Echinococcus granulosus

Abstract: S U M M A R YEchinococcus granulosus antigen B (AgB) is encoded by a gene family and is involved in the evasion of the host immune response. E. granulosus exists as a number of strains (G1-G10) that differ in biological characteristics. We used PCR-SSCP followed by DNA sequencing to evaluate sequence variation and transcription profile of AgB in 5 E. granulosus strains#. Twenty-four genomic sequences were isolated and clustered in 3 groups related to 2 of the 5 reported AgB genes. AgB4 genes were present in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 33 publications
2
32
0
3
Order By: Relevance
“…Kamenetzky et al [19] mentioned that no polymorphism in AgB2 genes was found in each strain but there was a substantial level of inter-strain variation in AgB2 related genes and that cysts from the same strain shared more genomic DNA than cysts from different strains. The high genetic similarity between the human and sheep isolates were confirmed by Jaccard's similarity coefficient and the dendrogram.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kamenetzky et al [19] mentioned that no polymorphism in AgB2 genes was found in each strain but there was a substantial level of inter-strain variation in AgB2 related genes and that cysts from the same strain shared more genomic DNA than cysts from different strains. The high genetic similarity between the human and sheep isolates were confirmed by Jaccard's similarity coefficient and the dendrogram.…”
Section: Discussionmentioning
confidence: 99%
“…Using PCR and RT-PCR, followed by cloning and sequencing, Arend et al [3] characterized a high degree of AgB2 sequence polymorphism between strains. Kamenetzky et al [19] using PCR-SSCP (single strand conformation polymorphism) followed by DNA sequencing to evaluate sequence variation and transcription profile of AgB2-coding genes in several human infecting strains of E. granulosus found a substantial level of inter-strain variation in AgB2-related genes between G1/G2 strain on one hand and G6/G7 and G5 on the other hand. Their finding was supported by a previous study using mitochondrial or nuclear markers which also grouped G1/G2 strains and G6/G7 strains as 2 separate groups leaving G5 strain outside but closer to the G6/G7 group [21].…”
Section: Discussionmentioning
confidence: 99%
“…E. granulosusspecific EgAgB is likely to be a key factor in the process of immune evasion, as the antigen is secreted and variable 34 . Encoded by a gene family, we found seven EgAgB genes in the genome, similar to in a previous report 13 .…”
Section: Evading Immune Recognition and Regulation Of Host Immunologimentioning
confidence: 99%
“…After establishment in the host, the hydatid cyst produces a large amount of AgB , which can alter the Th1/Th2 ratio from a predominant Th1 response in the early stage of infection to a Th2 response (Rigano et al, 2001), indicating that AgB is a modulator of the T cell response benefiting parasite survival. A number of studies have shown that AgB is encoded by a gene family and the antigen exhibits a high degree of genetic polymorphism (Haag et al, 2006;Rosenzvit et al, 2006;Kamenetzky et al, 2005), suggesting that the Echinococcus organisms have evolved antigenic variation-type mechanisms for escaping the host immune response.…”
Section: Regulatory T Cellsmentioning
confidence: 99%